EFEK WACANA TERORISME ATAS PELARANGAN MASUK WARGA NEGARA ISLAM KE AMERIKA SERIKAT - Jamaluddin, Ahmad (Journal of Islamic World and Politics, 2019)
This article examines relation between terrorism discourse and United States of America’s policy of restricting people from Islam countries to enter USA. Terrorism discourse is global problem, especially for Islam countries because they used to stigmatize as terrorist countries. In international relation field, this problem interferes Islam countries to build relationship with others. From this examination writer found conclusion that discourse of terrorism used by USA government to grab internal and external political support and in other hand increase the gap between leading countries and Islam as developing countries in international field.